PEMASARAN KARET (KAJIAN STRUKTUR, PERILAKU DAN PENAMPILAN PASAR) DI DESA SOREK DUA DAN TERANTANG MANUK KECAMATAN PANGKALAN KURAS KABUPATEN PELALAWAN - Afprida Yanti; Jum'atri Yusri; Novia Dewi (Indonesian Journal of Agricultural Economics, 2017)
This research aimed to analyze rubber marketing at subdistrict of Pangkalan Kuras with the structure approach, behavior, and market outlook. The research used survey method. The place was set purposively at Sorek Dua and Terantang Manuk village. The sample of the research was rubber farmers and all of the marketing institution of rubber at the research area. The result of the research concluded that there was only one marketing channel of the rubber at the area of the research. That was, the farmer sold the rubber product to the collector, the collector then sold it to the wholesaler of the rubber. Then, the wholesalers sold it to the manufacturer (rubber industry). The structure of rubber market at level of farmer was an Oligopsony Market. The characteristic of oligopsony was seen by the indicators as follow: 1) Number of the buyers in this case were the collectors, which were only a few; 2) The market share of the seller was not really different and the Herfindahl index value for the Sorek Dua and Terantang Manuk village were 0.348 and 0.5553 respectively. The farmer was a price taker and the selling price at the level of farmer was lowest than the selling price at the industry level. Total of market margin at Sorek Dua village was IDR 1837/kg with the detail of marketing cost of IDR 780.7/kg and the profit of IDR 1056.3/kg. The market margin of the Terantang Manuk village was   IDR 1740/kg, with the detail of marketing cost of IDR 825.85/kg and the profit of marketing institution was IDR 914.15/kg.